2019
DOI: 10.1371/journal.pone.0211882
|View full text |Cite
|
Sign up to set email alerts
|

Linking childhood emotional abuse and depressive symptoms: The role of emotion dysregulation and interpersonal problems

Abstract: Childhood abuse is a major public health problem that has been linked to depression in adulthood. Although different types of childhood abuse often co-occur, few studies have examined their unique impact on negative mental health outcomes. Most studies have focused solely on the consequences of childhood physical or sexual abuse; however, it has been suggested that childhood emotional abuse is more strongly related to depression. It remains unclear which underlying psychological processes mediate the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
73
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 73 publications
13
73
1
4
Order By: Relevance
“…For example, recent metaanalyses showed that emotional abuse and neglect were associated with greater risk for depression than were physical and sexual abuse, 7,52 and other studies have reported nonsignificant associations between both physical and sexual abuse with depressive symptoms. 53,54 That being said, as noted above, physical abuse and sexual abuse are often less frequently endorsed than other forms of maltreatment, and lower prevalence rates can attenuate the strength of their association with depression. Researchers have also posited that among individuals with a history of physical abuse and sexual abuse, distress may manifest in other ways, as these forms of abuse increase risk for other forms of psychopathology, namely posttraumatic stress disorder (PTSD) or sexual promiscuity, particularly in younger samples.…”
Section: Discussionmentioning
confidence: 98%
“…For example, recent metaanalyses showed that emotional abuse and neglect were associated with greater risk for depression than were physical and sexual abuse, 7,52 and other studies have reported nonsignificant associations between both physical and sexual abuse with depressive symptoms. 53,54 That being said, as noted above, physical abuse and sexual abuse are often less frequently endorsed than other forms of maltreatment, and lower prevalence rates can attenuate the strength of their association with depression. Researchers have also posited that among individuals with a history of physical abuse and sexual abuse, distress may manifest in other ways, as these forms of abuse increase risk for other forms of psychopathology, namely posttraumatic stress disorder (PTSD) or sexual promiscuity, particularly in younger samples.…”
Section: Discussionmentioning
confidence: 98%
“…both men and women; four studies (21,32,64,71) included female participants only and one study (52) included male participants only. Sample sizes ranged from 50 to 5,614 participants.…”
Section: Characteristics Of the Primary Studiesmentioning
confidence: 99%
“…In total, 13 studies examined emotion dysregulation as a potential mediating variable in the emotional abuse-depression link. Overall emotion dysregulation was examined in five studies (29,32,52,63,64). Two studies (32,64) reported that the effect of childhood emotional abuse on depressive symptoms was significantly mediated by emotion dysregulation measured by the DERS in emerging adult women.…”
Section: Emotion Dysregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who have secure attachments early in life can satisfy their needs through their own efforts while those with those with insecure attachments due to abuse and neglect tend to lack personal control affecting their self-efficacy. Abuse manifests in various forms such as emotional abuse, physical abuse, sexual abuse, psychological and social problems and neglect which collectively cause trauma and depression, substance dependency, problems in interpersonal relations leading to lowered self-esteem [42,43].…”
Section: Hindrances To Student Self-efficacymentioning
confidence: 99%